(NtEORIQ GRAFOW (B:s (NpER(B. (NS ANGL(B. /s - (NtATT(B, (NuILXQMs; (NgAWRILOW(B, (Ng(B.(Np(B.s ((NmOSKWA (B:s (NmIR (B,s, 1988)
(NpREDM(B. (NUKAZ(B.: (NS(B. 410-421s
Keywords: (NgRAFOW TEORIQ (B((NMAT(B.)s